TINJAUAN PENGISIAN JABATAN JAKSA AGUNG BERDASARKAN UU NO. 16 TAHUN 2004 DALAM MEWUJUDKAN INDEPEDENSI LEMBAGA KEJAKSAAN - Murtadha, Muhammad Ali; Aulia, Eza; Maulana, Jefrie (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
This study examines the normative regulation of Article 19 of Law Number 16 of 2004 concerning the appointment and dismissal of the Attorney General in Indonesia and its implications for prosecutorial independence. The research employs a normative juridical method using a statute approach, comparative approach, and conceptual approach. The findings indicate that the President's exclusive authority to appoint and dismiss the Attorney General without an adequate checks and balances mechanism poses a significant risk to the independence of the Attorney General’s Office. While the House of Representatives (DPR) has proposed legislative involvement in the appointment process, the final agreement between the government and DPR maintained full presidential authority. This raises concerns about potential political intervention and the dependency of the Attorney General on the executive branch. A comparative analysis reveals that other countries, such as the United States and Myanmar, implement stricter selection and dismissal mechanisms to ensure prosecutorial independence. In the United States, the Attorney General is appointed by the President with Senate approval and can be removed through an impeachment process. In Myanmar, the selection process involves independent oversight to maintain prosecutorial integrity. The study highlights the importance of implementing a stronger checks and balances system in Indonesia to prevent political influence and safeguard the professionalism of the Attorney General’s Office. Strengthening legal frameworks and ensuring institutional independence are crucial for maintaining the integrity of law enforcement. This study concludes that reforms in the Attorney General’s appointment mechanism are necessary to enhance the independence and credibility of the prosecutorial system in Indonesia.